Penerapan Asesmen Formatif Wayground Berbasis PBL Upaya Peningkatan Penalaran Kritis dan Kemampuan Menulis Siswa Kelas III SD - Ra'uf, Yahya Muhammad; Purwati, Panca Dewi (YASIN, 2025)
Although formative assessment and Problem-Based Learning (PBL) have received attention in previous studies, research that specifically examines the integration of formative assessment based on the interactive digital platform Wayground with PBL to enhance critical reasoning and sentence-writing skills in primary schools remains limited. This study aims to describe the implementation of Wayground formative assessment grounded in PBL in learning activities that involve arranging sentences from jumbled words and to analyze its effectiveness in improving critical reasoning and sentence-writing skills among third-grade primary school students. A mixed-methods approach with an embedded concurrent design was employed, involving 21 third-grade students of SD Negeri 1 Parikesit selected through purposive sampling. Data were collected using test instruments (pretest–posttest), observation, and questionnaires, and were analyzed using normalized gain (N-gain) techniques for quantitative data and data reduction, data display, and conclusion drawing for qualitative data. The results qualitatively indicate that most students demonstrate critical reasoning in the “good” category, as reflected in their ability to identify sentence structure errors, provide logical justifications, and independently correct mistakes. Quantitatively, there was a significant increase in the mean score from 62.0 to 81.5 with an N-gain of 0.51 (moderate category), an increase in the percentage of learning mastery from 65% to 90%, and 100% of students falling into the moderate N-gain category with no students in the low category. These findings contribute to the development of meaningful learning theory and constructivism, and broaden the understanding of digital technology integration in PBL-based formative assessment in primary schools. The study concludes that integrating digital formative assessment with problem-based learning models is essential for creating authentic, reflective, and inclusive learning experiences, and recommends that teachers and education practitioners adopt interactive digital platforms such as Wayground as formative assessment instruments that provide real-time feedback and adaptive scaffolding. The implications of this research include theoretical contributions in enriching the literature on digital formative assessment and PBL in primary schools, methodological contributions through the validation of Wayground as an alternative assessment instrument, and practical implications for teachers, schools, and policymakers in implementing innovative technology-based learning models, while opening further opportunities for exploration in other subjects, longitudinal studies, and comparative research across digital formative assessment platforms.